Basic theories and approaches in the study and analysis of change and transformation in the international system (A comparative study between realism, liberalism and constructivism) - Ameri, Haider Zayer Al (The International and Political Journal, 2022)
There have been many theories that have attempted to explain the change and transformation in the relations among states, those multiple, diverse, conflictual, competitive, cooperative and complementary relations. Those theories were not limited to study these transformations and changes in those relationships only, but also tried to predict the future of those relationships, their fate and transformations, as there are a number of old and new theories (or approaches) that tried to study and analyze those transformations in international relations such as the theory Realism, idealist theory, feminist theory, green theory, and English theoryAmong the most important foundations of this theory is that relations between states are based on the cultural variable or identity as an independent variable that influences and directs those relations, and that what results in the international system of conflict, competition, cooperation or integration is a dependent variable. (Dependent variables) of that independent variable, contrary to what theorists believe in the realist or idealist school. The (constructivist theory or the constructivist approach) can be applied in the study and analysis of most relations among states and the transformations and changes that occur to them, such as studying the transformation in relations between France and Germany after World War II from a situate of conflict to a case of cooperation, as well as other models that can be applied that theory on its, such as relations between Iraq and Iran, or Iraq and Kuwait .